Obscuring the Historical Origins of International Criminal Law in Australia: The Australian War Crimes Investigations and Prosecutions of Japanese, 1942–1951 - Morris, Narrelle (Torkel Opsahl Academic EPublisher, 2014)
As the Second World War slowly drew to a close in 1945, the Australian Government faced the difficult task of following through with numerous promises that it had articulated to the Australian public that it would vigorously pursue and bring all suspected Japanese war criminals to justice. While this laudable goal was loudly reiterated time and time again, the actual policies and practices by which Australia investigated and prosecuted Japanese for war crimes – what can be said to be part of the historical origins of international criminal law in Australia itself – have been, by comparison, relatively obscure. Indeed, the numerous war crimes investigations from 1942 and 300 Australian war crimes trials involving 812 principally Japanese accused war criminals that took place in Morotai, Wewak, Labuan, Rabaul, Darwin, Singapore, Hong Kong and on Manus Island from 1945 to 1951 had almost passed from popular memory until recently when, all of a sudden in this past decade, there has been a long overdue boom in war crimes studies in Australia.